Revolutionizing Pharmacy Practice: The Role of Automation and AI in Enhancing Patient Safety and Efficiency - Mona Yahia Mohammed Al Shahrani, Norah Hussein Ali Fardan, Shekhah Saad Habbash, Ghadah Khalid Ali Assiri, Alwah Ahmed Ali Asiri, Doaa Homeedy Aldrimi, Sarah Abdullah Alqahtani, Reem Ahmad Hassan Asiri (Journal of International Crisis and Risk Communication Research, 2024)
Pharmacy automation is emerging as a transformative tool in healthcare and improving patient outcomes, using digital technologies and artificial intelligence (AI) such as robotics and automated dispensing systems to improve medication distribution, reduce errors, manage inventory, and patient safety, thereby enhancing healthcare outcomes. Automated systems such as robots, AI-based algorithms, and remote dispensing services enable pharmacies to handle medication operations more efficiently and provide better patient services, especially in peripheral areas. Population growth and the rise of infectious and chronic diseases have led to increased demand for medicines and pharmaceutical services, which strongly drives the trend towards pharmacy automation and its effective role in reducing medication errors, improving efficiency, and meeting global needs. This review explores the benefits, challenges, and evolving role of pharmacists in a highly automated pharmacy environment. It also examines the integration of AI and robotics, highlighting their potential to reshape pharmacy practices and the overall health landscape.